Penerapan Rumah Kaca Sebagai Media Pengendali Lingkungan pada Budidaya Tanaman Hias - Dhia Fathyara Khalisha (Universitas Syiah Kuala, 2020)
Living in the era of industry as it is today, requires people to keep innovating and finding solutions of all needs. Various ways are made to create a new discovery or achievement for facilitating and accelerating human work, in this case an artificial environment. Those various artificial environments not only worked with the technology that has been developed, but with the support of structures as well as various materials and building systems that become the container or place of the new environment. Various media that can be used are, paranet, greenhouse, plastic house, and others. As one of the quite popular, greenhouses have certain requirements in order to get the right artificial environment. The requirements for the development are assisted by the support of various tools that needed, for example to regulate the temperature, humidity, and sunlight required. In addition to maintaining the environmental conditions contained in it, the greenhouse also has its own aesthetic value. With the nature of exposed structure, greenhouse much in demand as the main part of the building design.